Exploring flipped teaching practices in Bangladeshi ESL secondary classrooms - Islam, Jahirul; Abd Rahman, Siti Nadhirah (Faculty of Educational Studies, Universiti Putra Malaysia, 2024)
Flipped classroom is a form of instructional environment that allows educators to consistently reach out and improve students’ differentiated learning. The ESL classrooms extensively employ flipped teaching practices to extend and enhance classroom instructions. Such methodologies require teachers with multiple abilities to apply their most effective teaching practices to successfully implement flipped classroom. The purpose of this study is to examine flipped teaching practices in Bangladeshi ESL secondary classes, specially to explore instructors' flipped classroom experiences. Thus, this study focuses on the various forms of flipped teaching practised by instructors such as pedagogical instruction, teaching and learning experiences. This qualitative research adopts a case study approach to holistically understand participants’ opinions of contemporary phenomena. Approximately 11 ESL teachers would be selected for entire data collection process using purposeful sampling. Multiple data collection phases like semi-structure interview, and document analysis would involve to perform the study process. As English is widely used in schools, colleges, and universities, the elicited outcomes would serve as guidelines for educational institutions at all levels in Bangladesh. Education policymakers who intend to create a digital education system in the country can also improve the ESL pedagogical practice with these guidelines. Therefore, this empirical work could propose the most effective means of integrating both theories with the ESL pedagogy flipped methods.